Variation of Ozone, Carbon Monoxide, and Oxides of Nitrogen at Bengaluru, India - Dhanya, G.; Pranesha, T. S.; Nagaraja, K.; Chate, D. M.; Beig, G. (Journal of Scientific Research, 2022)
The present study analyses the continuous in-situ observations of surface ozone (O3), carbon monoxide (CO), and nitrogen oxides (NOX) conducted in an urban location, Bengaluru, India, during the year 2019 (January to December). The seasonal concentration of O3 fluctuated with the highest concentrations in the summer (39.6 ppbv) and winter (40.4 ppbv) and the lowest concentrations during the monsoon (16.8 ppbv). The seasonal mixing ratio of CO showed the highest value in post-monsoon (1.71 ppmv) and lowest during monsoon (0.79 ppmv). The seasonal trend of NOX showed highest in winter (56.8 ppbv) and lowest in monsoon (22.5 ppbv). The monthly mixing ratios of O3, CO, and NOX showed distinct variability, which may be attributed to changing anthropogenic activities, planetary boundary layer processes, and local meteorology. O3 was significantly related to temperature but inversely associated with relative humidity and wind speed. The association between CO, NOX with relative humidity, temperature, wind speed showed discrete results. The (dO3/dt) in the morning and evening duration were about 5.0 ppbv/h and -4.1 ppbv/h respectively.